Interaction between SCO-spondin and low density lipoproteins from embryonic cerebrospinal fluid modulates their roles in early neurogenesis - Vera, América; Recabal, Antonia; Saldivia, Natalia; Stanic, Karen; Torrejón, Marcela; Montecinos, Hernán; Caprile, Teresa (Frontiers in Neuroanatomy, 2015)
During early stages of development, encephalic vesicles are composed by a layer of neuroepithelial cells surrounding a central cavity filled with embryonic cerebrospinal fluid (eCSF). This fluid contains several morphogens that regulate proliferation and differentiation of neuroepithelial cells. One of these neurogenic factors is SCO-spondin, a giant protein secreted to the eCSF from early stages of development. Inhibition of this protein in vivo or in vitro drastically decreases the neurodifferentiation process. Other important neurogenic factors of the eCSF are low density lipoproteins (LDL), the depletion of which generates a 60% decrease in mesencephalic explant neurodifferentiation. The presence of several LDL receptor class A (LDLrA) domains (responsible for LDL binding in other proteins) in the SCO-spondin sequence suggests a possible interaction between both molecules. This possibility was analyzed using three different experimental approaches: (1) Bioinformatics analyses of the SCO-spondin region, that contains eight LDLrA domains in tandem, and of comparisons with the LDL receptor consensus sequence; (2) Analysis of the physical interactions of both molecules through immunohistochemical colocalization in embryonic chick brains and through the immunoprecipitation of LDL with anti-SCO-spondin antibodies; and (3) Analysis of functional interactions during the neurodifferentiation process when these molecules were added to a culture medium of mesencephalic explants. The results revealed that LDL and SCO-spondin interact to form a complex that diminishes the neurogenic capacities that both molecules have separately. Our work suggests that the eCSF is an active signaling center with a complex regulation system that allows for correct brain development.